Protest Visual Arts in Iran from the 1953 Coup to the 1979 Islamic Revolution - Zabolinezhad, Hoda; Shad Qazvini, Parisa (International Journal of Criminology and Sociology, 2022)
There have been conducted a few numbers of researches with protest-related subjects in visual arts in a span between the two major unrests, the 1953 Coup and the 1979 Islamic Revolution. This study tries to investigate how the works of Iranian visual artists demonstrate their reactions to the 1953 Coup and progresses towards modernization that occurred after the White Revolution of Shāh in 1963. The advent of the protest concept has coincided with the presence of Modern and Contemporary art in Iran when the country was occupied by allies during the Second World War. The 1953 Coup was a significant protest event that motivated some of the artists to react against the monarchy’s intention. Although, poets, authors, journalists, and writers of plays were pioneer to combat dictatorship, the greatest modernist artists of that time, impressed by the events after the 1953 Coup, just used their art as rebellious manifest against the governors.